Pendekatan Hermeneutika Paul Ricoeur Dalam Diskursus Studi Islam Dan Tafsir - Sholehah, Marwa Maratus; Mustofa, Ahmad (Aqlania, 2024)
Abstract: This study aims to explore Paul Ricoeur's thinking and see how far Paul Ricoeur's hermeneutics is used as an approach. Paul Ricoeur's Hermeneutics is a philosophical hermeneutics whose approach is very rarely used by Exegesis academics. The research was carried out using a literature approach. Data collection was carried out through literature studies. The results of this study confirm that Paul Ricoeur's approach has been applied in various fields of study, including Islamic studies and interpretation. However, in some parts, the methodological flow of Ricoeur's hermeneutics is not used in its entirety. Some emphasize linguistic aspects, symbols and myths. Meanwhile, several scientific works use the methodological flow offered by Ricoeur in its entirety, including, Objectification of structures, Distansiasi (distance), World of Texts, and Apppropriation. Ricoeur's approach in Islamic studies is quite widely studied by academics, but in the study of the Qur'an and exegesis, Ricoeur's approach is only limited to being used as a comparison with other mufassir thoughts. In short, Ricoeur's approach is not used as a tool for interpreting the Qur'an like some other hermeneutic approaches.